Virtual reality delivered exposure for fear of needles: a small-scale pilot - Caltabiano, Anna; Burke, Taylor; Nesi, Jacqueline; Di Simplicio, Martina; van Zalk, Nejra (Frontiers in Psychiatry, 2025)
BackgroundFear of needles significantly impacts individual and public health by leading many adults to avoid necessary medical procedures, including vaccinations and blood tests. Virtual Reality Exposure-Based Therapy has shown promise as an effective and accessible intervention for anxiety disorders but remains under-explored.ObjectivesThis study aimed to evaluate the efficacy and acceptability of a single-session virtual reality intervention targeting fear of needles in adults.MethodsA total of 62 adults reporting needle fear were recruited into experimental (n = 32) and online comparison groups (n = 30). The experimental group completed one Virtual Reality Exposure-Based Therapy session, which comprised of two self-paced virtual reality exposures simulating medical needle procedures. Anxiety and affect were assessed at baseline, during, and immediately following virtual reality exposures, and at a one-month follow-up. Acceptability, usability, presence, plausibility, and virtual reality sickness were also measured.ResultsThe intervention successfully elicited anxiety during exposure. At one-month follow-up, a modest but statistically significant reduction in symptom severity was observed on one measure (Specific Phobia Questionnaire), though no significant change was noted in life interference or on another severity measure (Medical Fears Survey). Participants rated the intervention highly in terms of usability and acceptability, although some reported symptoms of virtual reality sickness (e.g., disorientation, motion sickness).ConclusionsVirtual Reality Exposure-Based Therapy appears to be an effective and highly acceptable intervention for reducing immediate anxiety related to needle exposure, demonstrating strong potential as a scalable, accessible alternative to traditional exposure therapy. However, further research is necessary to confirm these findings, optimize intervention protocols, and examine long-term effectiveness for fear of needles.